2015
DOI: 10.1016/j.jtcme.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antimalarial activity of the crude root and fruit extracts of Croton macrostachyus (Euphorbiaceae) against Plasmodium berghei in mice

Abstract: Euphorbiaceae (Croton macrostachyus H.; 巴豆 bā dòu) is used in Ethiopian folklore medicine for the treatment of malaria, gonorrhea, diabetes, wounds, fungal infections, and helminths. No scientific investigations have been performed to substantiate these claims. This study aimed to investigate the in vivo antiplasmodial activity of 80% methanol extract of the fruit and the root of Croton macrostachyus H. in a rodent model of malaria. The rodent malaria parasite Plasmodium berghei was used to inoculate healthy 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 23 publications
2
49
0
Order By: Relevance
“…The acute toxicity study crude and the solvent fraction of leaf indicated that the extract caused no mortality and no visible signs of overt toxicity at doses of 2 and 5g/kg within the 14 days follow up periods. However, The crude extracts from the fruit and root did not show mortality and sign of toxicity up to a dose of 2g/kg within the 14 days (28)(29)(30). Sub-acute toxicity test of methanol and aqueous extracts of C. macrostachyus leaf on day 4 showed no statistically significant difference (P>0.05) in all the hematological parameters.…”
Section: Safety and Toxicitymentioning
confidence: 83%
See 2 more Smart Citations
“…The acute toxicity study crude and the solvent fraction of leaf indicated that the extract caused no mortality and no visible signs of overt toxicity at doses of 2 and 5g/kg within the 14 days follow up periods. However, The crude extracts from the fruit and root did not show mortality and sign of toxicity up to a dose of 2g/kg within the 14 days (28)(29)(30). Sub-acute toxicity test of methanol and aqueous extracts of C. macrostachyus leaf on day 4 showed no statistically significant difference (P>0.05) in all the hematological parameters.…”
Section: Safety and Toxicitymentioning
confidence: 83%
“…Maximum inhibition (82.3%) was attained with 600mg/kg dose of the fraction. The other investigation by Laychiluh et al, 28 Indicated that, the fruit extract 600mg and root extract 600mg of C. macrostachyus exhibited a significant parasite suppression 83%and 88% respectively, compared to the other doses, the root extract had better suppressive activity and it increased survival time better than the fruit extract. Analysis of the rectal temperature revealed that 80% methanolic fruit extract of C. macrostachyus significantly prevented the reduction of temperature in a dose-dependent manner (p<0.01 for fruit 200mg and fruit 400mg; p<0.001 for fruit 600mg).…”
Section: Efficacymentioning
confidence: 88%
See 1 more Smart Citation
“…Unlike water extracts, alcoholic extracts of the leaves and seeds of A. indica were effective against P. falciparum in vivo. Mekonnen (2015) described the use of Croton macrostachyus Hochst. ex Delile root and fruit extracts for the treatment of malaria.…”
Section: Ethiopiamentioning
confidence: 99%
“…1 Malaria is preventable and curable; however, it still remains a major cause of mortality and morbidity especially in the developing countries. 2 Five species of Plasmodium parasite have been identified to cause the mosquito-borne disease in humans including P. falciparum, P. ovale, P. malariae, P. vivax and P. knowlesi. 3 Plasmodium falciparum is the deadliest parasite responsible for the majority of malaria-related morbidity and mortality with a significant social and economic impact in developing countries including Nigeria.…”
Section: Introductionmentioning
confidence: 99%